Regulatory Mechanisms of lncRNAs and Their Target Gene Signaling Pathways in Laryngeal Squamous Cell Carcinoma - Li, Wei; Chen, Yu; Nie, Xuqiang (Frontiers in Pharmacology, 2020)
Laryngeal squamous cell carcinoma (LSCC) is a common malignant tumor that occurs in the head and neck. People living in areas with serious air pollution and those who smoke and drink for a long time belong to high-risk groups. Although great progress has been made in chemotherapy, radiotherapy and molecular targeted therapy in recent years, the prognosis of patients is still not good. The proliferation, invasion and apoptosis of LSCC are controlled by many factors, which are the key factors influencing the prognosis of patients. Previous researches have demonstrated that long non-coding RNAs (lncRNAs) can be used as oncogenes or tumor suppressor genes in the occurrence and development of cancer, and regulate cancer through various ways including epigenetic regulation and post-transcriptional regulation. The characteristics and roles of lncRNAs in LSCC, however, are not clear. In this review, we will discuss the role and function of lncRNAs in the proliferation, invasion and apoptosis of LSCC, and analyze the relationship between lncRNAs and lncRNA- regulated signaling pathways in LSCC pathological process. The difficulties faced by the related research of LSCC are discussed. It provides reference ideas for the molecular mechanism research of LSCC targeting lncRNA and its signaling pathways, the development of clinical prevention and therapeutic drug and individualized treatment. Thereby improving the quality of life of patients.